The IL-33/ST2 Axis in Immune Responses Against Parasitic Disease: Potential Therapeutic Applications - Ryan, Nathan; Anderson, Kelvin; Volpedo, Greta; Varikuti, Sanjay; Satoskar, Monika; Satoskar, Sanika; Oghumu, Steve (Frontiers in Cellular and Infection Microbiology, 2020)
Parasitic infections pose a wide and varying threat globally, impacting over 25% of the global population with many more at risk of infection. These infections are comprised of, but not limited to, toxoplasmosis, malaria, leishmaniasis and any one of a wide variety of helminthic infections. While a great deal is understood about the adaptive immune response to each of these parasites, there remains a need to further elucidate the early innate immune response. Interleukin-33 is being revealed as one of the earliest players in the cytokine milieu responding to parasitic invasion, and as such has been given the name ‘alarmin’. A nuclear cytokine, interleukin-33 is housed primarily within epithelial and fibroblastic tissues and is released upon cellular damage or death. Evidence has shown that interleukin-33 seems to play a crucial role in priming the immune system towards a strong T helper type 2 immune response, necessary in the clearance of some parasites, while disease exacerbating in the context of others. With the possibility of being a double-edged sword, a great deal remains to be seen in how interleukin-33 and its receptor ST2 are involved in the immune response different parasites elicit, and how those parasites may manipulate or evade this host mechanism. In this review article we compile the current cutting-edge research into the interleukin-33 response to toxoplasmosis, malaria, leishmania and helminthic infection. Furthermore, we provide insight into directions interleukin-33 research may take in the future, potential immunotherapeutic applications of interleukin-33 modulation and how a better clarity of early innate immune system responses involving interleukin-33/ST2 signaling may be applied in development of much needed treatment options against parasitic invaders.